Antimicrobial, Antioxidant and Cytotoxic Activities of Callistemon citrinus (Curtis) Skeels - Haque, Md Enamul; Sultana, Afrin; Shibib, Biazid Alam; Islam, Md Mirazul (Dhaka University Journal of Pharmaceutical Sciences, 2012)
The petroleum ether, ethyl acetate and methanol extracts of the stem bark of Callistemon citrinus were subjected to screenings for antimicrobial and antioxidant activities and brine shrimp lethality. The ethyl acetate extract and its column fractions XVIII and XIV exhibited moderate antimicrobial activity, while the methanol extract revealed significant antioxidant activity having IC50 of 3.84 ?g/ml. The methanol extract and fraction-II showed potent cytotoxic its cytotoxicity with the LC50 of 11.27 and 11.35 ?g/ml, respectively. DOI: http://dx.doi.org/10.3329/dujps.v11i1.12487 Dhaka Univ. J. Pharm. Sci. 11(1): 51-54, 2012 (June)